1995
DOI: 10.1002/cm.970310306
|View full text |Cite
|
Sign up to set email alerts
|

Traction forces in locomoting cells

Abstract: A means of determining quantitative maps of the tractions exerted by locomoting cells on a substratum has been developed. This method is similar to the Harris silicone substratum assay [Harris et al., 1980: Science 208:177-179], but uses an improved non-wrinkling film that deforms more predictably in response to traction forces. The method also utilizes a mathematical analysis of rubber deformation to produce the final map of the distribution of tractions. The resulting maps consistently showed that fish kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 21 publications
9
144
1
Order By: Relevance
“…It is conceivable that wrinkle-producing fibroblasts exert only the minimum force necessary to deform these weak surfaces; therefore, the use of elastomers with gradually increasing stiffness is crucial to determine their maximum contractile potential. Highly compliant elastomers have been wrinkled by a large proportion of ␣-SMAnegative fibroblasts consistent with the wrinkling capability of numerous cell types (Lee et al, 1994;Oliver et al, 1995). With the use of stiffer substrates, we determined a threshold of ϳ4 N that discriminates between these relatively weak traction forces and higher contractile forces (Roy et al, 1999); this threshold is only surpassed by ␣-SMA-positive fibroblasts.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is conceivable that wrinkle-producing fibroblasts exert only the minimum force necessary to deform these weak surfaces; therefore, the use of elastomers with gradually increasing stiffness is crucial to determine their maximum contractile potential. Highly compliant elastomers have been wrinkled by a large proportion of ␣-SMAnegative fibroblasts consistent with the wrinkling capability of numerous cell types (Lee et al, 1994;Oliver et al, 1995). With the use of stiffer substrates, we determined a threshold of ϳ4 N that discriminates between these relatively weak traction forces and higher contractile forces (Roy et al, 1999); this threshold is only surpassed by ␣-SMA-positive fibroblasts.…”
Section: Discussionmentioning
confidence: 86%
“…A second stiff needle (Ն50 N/ m) was used to fix the substrate at a distance of 200 m, simulating the substrate-pinching of bipolar cells. The force required to produce first wrinkles on different silicone substrates was calculated from the flexible needle stiffness ( N/ m) and deflection ( m; Oliver et al, 1995) on 15 different regions. LFs were then grown on these substrates and immunostained, and the percentage of wrinkling cells of ␣-SMA-positive LFs and of ␣-SMA-negative LFs were calculated separately as described above.…”
Section: Deformable Silicone Substrates and Single Cell Force Measurementioning
confidence: 99%
“…Traction forces during keratocyte locomotion were first studied by Jacobson and colleagues (Lee et al, 1994;Oliver et al, 1995;Dembo et al, 1996) with the use of a modification of the method developed by Harris et al (1980) in which cell forces applied to silicone rubber substrata produce deformations visible in the light microscope. Lee et al (1994) were able to fabricate elastic substrata with higher compliance than those used in earlier studies on fibroblasts (Harris et al, 1980), allowing lower forces to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (1994) were able to fabricate elastic substrata with higher compliance than those used in earlier studies on fibroblasts (Harris et al, 1980), allowing lower forces to be detected. In addition, strain in the elastic substratum was quantified by monitoring the movements of markers incorporated into its surface (Harris, 1984;Lee et al, 1994;Oliver et al, 1995;Dembo et al, 1996) rather than wrinkles, as had been used originally (Harris et al, 1980). Their results showed that lateral forces, directed inward toward the center of the cell, were dominant during forward locomotion (Lee et al, 1994;Oliver et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, the stalling force of a filament, at which the elongation velocity drops to zero, could be estimated to a few piconewtons (6)(7)(8). Comparatively, forces of a few nanonewtons are required to stall the migration of cells (9,10) or Listeria comet tails (11). This difference of three orders of magnitude points to the need for a large number of cooperating filaments to generate high forces in protrusive structures.…”
mentioning
confidence: 99%